Today’s youth subcultures: Resistance or corporation - BULENT KABAS (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This research aims to analyze the recent changes in two different youth subcultures. Subcultures today contribute heavily to the multifaceted framework that exists today. However, they lack any sort of coherence outside of the realm of mass culture. In other words, youth subcultures become embedded in the system they once protested through mainstream media.Methodology: This research relies on information gleaned from a thorough review of the relevant literature.Findings: Existing facts and data are critically evaluated, revealing that modern subcultures are formed with a structure to help individuals find the content most appropriate to their desires and needs, satisfying them aesthetically and in terms of other senses and enhancing the relationship of cultures with life.Novelty/Implications: Instead of using the term